Disputed Archival Heritage - Lowry, James (Routledge, 2022)
Disputed Archival Heritage brings important new perspectives into the discourse on displaced archives. In contrast to shared or joint heritage framings, the book considers the implications of force, violence and loss in the displacement of archival heritage. With chapters from established and emerging scholars in archival studies, Disputed Archival Heritage extends and enriches the conversation that started with the earlier volume, Displaced Archives. Advancing novel theories and methods for understanding disputes and claims over archives, the volume includes chapters that focus on Indigenous records in settler colonial states; literary and community archives; sub-national and private sector displacements; successes in repatriating formerly displaced archives; comparisons with cultural objects seized by colonial powers and the relationship between repatriation and reparations. Analysing key concepts such as joint heritage and provenance, the contributors unsettle Western understandings of records, place and ownership. Disputed Archival Heritage speaks to the growing interest in shared archival heritage, repatriation of cultural artefacts and cultural diasporas. As such, it will be a useful resource for academics, students and practitioners working in the field of archives, records and information management, as well as cultural property and heritage management, peace and conflict studies and international law.